DEVELOPMENT OF A MORE THERMOSTABLE PECTIN ACETYLESTERASE FROM ERWINIA CAROTOVORA ATROSEPTICUM - Wesley, Aaron M. (My University, 2012)
Pectin acetylesterase (PAE) catalyzes deacetylation of pectin, yielding acetate and polygalacturonate. The PAEY gene of Erwinia atrosepticum was cloned and the strategy of directed evolution was utilized to construct a more thermostable variant of the enzyme for use in biofuels production in a biorefinery. Libraries of PAEY mutants were screened for thermostability using the para-nitrophenol acetate (pNPA) assay. A thermostable mutant was discovered. This mutant had two amino acid substitutions, Gly48Asp and Arg297Gly. The mutation Arg297Gly conferred a 2°C increase in Tₘ, while the combination of mutations resulted in a 2 to 3-fold increase in specific activity, suggesting an interaction between the mutations. Although sharing 61% sequence identity with another characterized PAE (Erwinia chrysanthemi), PAEY from E. atrosepticum did not exhibit activity on natural substrate (pectin). These results suggest the possibility that, while an acetylesterase, the putative PAEY enzyme of E.atrosepticum has diverged from a pectin acetylesterase in physiological function.